Manajemen Sekolah di Era Society 5.0 dalam Meningkatkan Kualitas dan Produktivitas Sumber Daya Manusia - Ahmad Khoirudin; Nur Khoiri; Rizky Bagus Fahreza; Indra Faizatun Nisa’ (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
The principal is the main key in an educational institution so that the performance or leadership of the principal really determines the educational institution in terms of the quality of an educational institution. In line with technological advances that are increasingly rapid and rapid, especially in the era of society 5.0, it is very challenging for school principals to organize or manage schools so that they can improve their overall quality. This research aims to find out and examine the importance of school management in the era of society 5.0 in an effort to increase educational efficiency and productivity. This research uses a method of literature study from several articles and books related to school management in the era of society 5.0. This method uses a systematic literature review to identify, analyze, evaluate, and draw conclusions from various research results related to the topic discussed. This method centers on creating a solid foundation for solving problems. The results of the discussion show that school principals are required to have good digital literacy skills and high creativity along with technological developments in order to be able to face the challenges of the rapid rise of technology. The research results show the importance of school management in the era of society 5.0. in improving the quality and productivity of human resources.